Loss of control of asthma following inhaled corticosteroid withdrawal is associated with increased sputum interleukin-8 and neutrophils - Kittipong Maneechotesuwan (2018)
Background: The role of neutrophils in exacerbations of asthma is poorly understood. We examined the effect of withdrawal of inhaled corticosteroids on sputum inflammatory indexes in a double-blind study in patients with moderate, stable asthma. Methods: Following a 2-week run in period, 24 subjects were randomized to receive either budesonide (400 μg bid) or placebo, and the study was continued for another 10 weeks. Results: Loss of asthma control developed in 8 of 12 patients over the 10-week period of steroid withdrawal, whereas only 1 of 10 patients with budesonide treatment had exacerbations. Those with an exacerbation had increased sputum interleukin (IL)-8 (p < 0.0001) and increased sputum neutrophil numbers (p < 0.0001) compared to those without an exacerbation. The significant elevation in sputum IL-8 and neutrophil counts initially occurred 2 weeks prior to an exacerbation. Sputum neutrophilia correlated positively with changes in IL-8 levels (r2= 0.76, p = 0.01). Conclusions: Rapid withdrawal of inhaled corticosteroids results in an exacerbation of asthma that is preceded by an increase in sputum neutrophils and IL-8 concentrations, in contrast to an increase in eosinophils reported in previous studies in which inhaled steroids are slowly tapered.